Psychometric evaluation of computer-administered tension scales for weight management in rural telehealth settings. - Kramer KL (Psychometric Evaluation of Computer-administered Tension Scales for Weight Management in Rural Telehealth Settings, 2007)
Background. Currently, measures are lacking to assess the parameters of the multifaceted problem of overweight and obesity. Earlier study suggests that measures are needed to assess overeating tension, exercise tension, and feelings tension as contributing factors to the obesity epidemic in America. Purpose. The purpose of this pilot study was to evaluate the computer-administration and psychometric analysis of the three tension scales, Overeating Tension, Exercise Tension and Feelings Tension, in three rural settings served by the University of Kansas Telehealth Program. Methods. Computer-administration measures were evaluated for readability, content validity, usability, human-computer interface, and performance (Phase 1) and psychometric evaluations of internal consistency reliability and construct validity were conducted with 61 participants (Phase 2). Results: Phase 1 established: readability at a 5th grade level using a linguistics expert; content validity using reversal theory experts, content validity index, and kappa score; usability, human-computer interface, and performance using expert evaluation; and participant evaluation. In Phase 2, internal consistency reliability and construct validity were supported. Participants with higher Body Mass Index (BMI; [kg]/height [m2]) had higher tension scores on the Overeating Tension, Exercise Tension, and Feelings Tension Scales compared to those with lower BMI. Conclusions. This study established the computer-administration, internal consistency reliability and content validity of the three scales. Future work will continue to establish convergent validity of these three scales and their ability to assess overeating tension, exercise tension and feelings tension in rural telehealth weight management patients.